P.24: Relation between Recognition of Illumination and Depth Perception. Issue 1 (1st July 2013) - Kaji, Hiroyuki; Oba, Kentaro; Nagai, Kazushige; Iwauchi, Ken‐ichi; Tanaka, Seiichi; Saito, Sakae; Ishikawa, Tomoharu; Ayama, Miyoshi
Abstract: We investigated quantitative relation between shading on the surface and the perceptual evaluation of depth using primary and secondary cylindrical objects using 2D and 3D displays. Results showed that luminance gradient of the secondary object that gives most natural protrusive perception as a cylinder is the same as that of the primary object. Interestingly, the cases where luminance of brighter part of the secondary stimulus is relatively low, they are less accepted when it is supposed to be in front of the primary object.